Вы находитесь на странице: 1из 7

Expressing physical relations in accelerated

frames
written by Benjamin Preiss
December 26, 2017

Abstract
Certain laws in physics, like for example Newtons three axioms, only
apply to quantities expressed in an inertial frame. Sometimes however it
happens that it is easier for us to express these quantities in a somewhat
rotated and shifted reference frame. So now the question is, how do they
relate in that case, according to a physical law?
To answer this question there are some preparations and assumptions which
have to be done first:

1. We define the following notation:


~a |i vector ~a with reference to the inertial frame
~a |r vector ~a with reference to the moving frame
2. For our derivation we define an inertial and a moving reference frame,
which shall be shifted and rotated with respect to eachother by vectors
m~ 0 (t) |i ~j0 (t) |i

and Matrix RT respectively.

1
Figure 1: relation of vectors in different reference frames

It can be seen by inspection:


m(t)
~ |i = R · ~n(t) |r + m
~ 0 (t) |i ~j(t) |i = R · ~k(t) |r + ~j0 (t) |i

3. Our physical law is an equation of the form


d d
f (m(t)
~ |i ,
m(t)
~ |i ) = g(~j(t) |i , ~j(t) |i )
dt dt
and for any matrix D(t):
d d
D(t) · f (m(t)
~ |i , m(t)
~ |i ) = f (D(t) · m(t)
~ |i , D(t) · m(t)
~ |i )
dt dt
d d
D(t) · g(~j(t) |i , ~j(t) |i ) = g(D(t) · ~j(t) |i , D(t) · ~j(t) |i )
dt dt
4. We assume to be in the situation, where it is much easier for us to express
d ~j(t), d ~j(t)
m(t),
~ m(t)
~
dt dt
in the moving frame (because they are somehow aligned throughout time
with a rotating frame axis or so). Because it saves us time, we must not
calculate them in the inertial frame.

2
Now due to our fourth assumption we can rewrite our law:
T d T T d
R · f (m(t)
~ |i , m(t)
~ |i ) = f (R · (R · ~
n(t) |r + m
~ 0 (t) |i ), R · (R · ~
n(t) |r + m
~ 0 (t) |i ))
dt dt
T d
= n(t) |r + m
f (~ ~ 0 (t) |r , R · (R · ~
n(t) |r + m
~ 0 (t) |i ))
| {z } dt
| {z }
α
~ (t)
~
β(t)

T d T T d
R · g(~j(t) |i , ~j(t) |i ) = g(R · (R · ~
k(t) |r + ~j0 (t) |i ), R · (R · ~
k(t) |r + ~j0 (t) |i ))
dt dt
T d
= g(~
k(t) |r + ~j0 (t) |r , R · (R · ~
k(t) |r + ~j0 (t) |i ))
| {z } dt
| {z }
~
γ (t)
~
(t)

such that

f (~ ~
α(t), β(t)) = g(~γ (t),~(t))

Note, that for any vector ~v :


d d T d
RT · ~v (t) |i 6= R · ~v (t) |i = ~v (t) |r
dt dt dt

Now that we know α ~


~ (t) and ~γ (t) it remains to simplify β(t) and ~(t). We will
~
only do so for β(t) as it is similar for ~(t):

~ d
β(t) = RT · (R · ~n(t) |r + m
~ 0 (t) |i )
dt
d d
= RT · (R · ~n(t) |r ) + RT · m ~ 0 (t) |i
dt dt
d d d
= RT · R · ~n(t) |r + RT · R · ~n(t) |r + RT · ~ 0 (t) |i
m
dt dt dt
d d d
= RT · R · ~n(t) |r + RT · R · ~n(t) |r + RT · m ~ 0 (t) |i
dt dt dt
There are still some things to discover. But first here are some simple statements
from the field of linear algebra:

because R is a rotation matrix the following holds true:

R−1 = RT

RT · R = R · RT = 1
Differentiating the last equation with respect to time yields (again using product
rule):
d d d
RT · R = − RT · R = −(RT · R)T
dt dt dt
Defining the matrix
d
S = RT · R
dt

3
we see that S must be antisymmetric:
 
0 −s3 s2
S =  s3 0 −s1  = −ST
−s2 s1 0
 
s1
For a vector ~s =  s2  we see that
s3
   
0 −s3 s2 s1
S =  s3 0 −s1  =  s2  × = ~s×
−s2 s1 0 s3

Substituting S for RT · d ~
I3x3 for RT · R and β(t) for RT · d
|i
dt R, dt m(t)
~ we get:

d d d
RT · m(t)
~ |i = S · ~n(t) |r + ~n(t) |r + RT · m ~ 0 (t) |i
dt dt dt
What could be a physical interpretation of this expression? Because an inertial
d
frame is not accelerated per definition, RT · dt m(t)
~ |i is the absolute change of
d
m(t),
~ with dt m(t)
~ |i being expressed in the moving frame. The absolute change
of vector m(t)
~ can be split into a rotational part (due to rotation of moving
frame) and another part (due to change of ~n(t) in the moving frame). The
rotation is represented by S = ~s×. It will turn out, that ~s is just the angular
velocity vector ω~ expressed in the moving frame. Here is the proof:

In the following derivation · shall be used as the matrix, ∗ as the dot and × as
the cross product operator.
For any vector ~v the representations in inertial and rotating frame are linked by
R:

~v |i = R · ~v |r

4
Figure 2: ~n(t) decomposed

R can be written as
 
~xr |i ∗ ~xi |i ~yr |i ∗ ~xi |i ~zr |i ∗ ~xi |i
R =  ~xr |i ∗ ~yi |i ~yr |i ∗ ~yi |i ~zr |i ∗ ~yi |i 
~xr |i ∗ ~zi |i ~yr |i ∗ ~zi |i ~zr |i ∗ ~zi |i
Therefore we understand that the columns of R are just the rotating basis
vectors expressed in the inertial frame:
 
R = ~xr |i ~yr |i ~zr |i
 
T
(~xr |i )
RT =  (~yr |i )T 
 
T
(~zr |i )
d  d d d

R = dt ~ xr |i dt ~yr |i dt ~zr |i
dt  
T d T d T d
(~xr |i ) · dt ~xr |i (~xr |i ) · dt ~yr |i (~xr |i ) · dt ~zr |i
d
RT · R =  (~yr |i )T · dt d T
~xr |i (~yr |i ) · dt d T
~yr |i (~yr |i ) · dt d
~zr |i 
 
dt T d T d T d
(~zr |i ) · dt ~xr |i (~zr |i ) · dt ~yr |i (~zr |i ) · dt ~zr |i
d d d
 
~xr |i ∗ dt ~xr |i ~xr |i ∗ dt ~yr |i ~xr |i ∗ dt ~zr |i
d d d
=  ~yr |i ∗ dt ~xr |i ~yr |i ∗ dt ~yr |i ~yr |i ∗ dt ~zr |i 
d d d
~zr |i ∗ dt ~xr |i ~zr |i ∗ dt ~yr |i ~zr |i ∗ dt ~zr |i
d d d
  
Because dt ~xr |i ⊥ (~xr |i ), dt ~yr |i ⊥ (~yr |i ) and dt ~zr |i ⊥ (~zr |i ):
d d
 
0 ~xr |i ∗ dt ~yr |i ~xr |i ∗ dt ~zr |i
d
RT · R =  ~yr |i ∗ dt d
~xr |i 0 d
~yr |i ∗ dt ~zr |i 
dt d d
~zr |i ∗ dt ~xr |i ~zr |i ∗ dt ~yr |i 0

5
d
That confirms our previous discovery of S = RT · dt R being skew-symmetric.
~ r |i shall be the angular velocity of the moving with respect to the inertial
ω
frame ω ~ r |i expressed in the inertial frame. In S we replace:
d
~xr |i = ~ r |i × ~xr |i
ω
dt
d
~yr |i = ~ r |i × ~yr |i
ω
dt
d
~zr |i = ~ r |i × ~zr |i
ω
dt
 
0 ~xr |i ∗ (~
ωr |i × ~yr |i ) ~xr |i ∗ (~ωr |i × ~zr |i )
S =  ~yr |i ∗ (~ωr |i × ~xr |i ) 0 ~yr |i ∗ (~
ωr |i × ~zr |i ) 
~zr |i ∗ (~
ωr |i × ~xr |i ) ~zr |i ∗ (~
ωr |i × ~yr |i ) 0
Using the identity for the parallelepipedal product:
~xr |i ∗ (~
ωr |i × ~yr |i ) = ~ r |i ∗ (~yr |i × ~xr |i )
ω
~xr |i ∗ (~
ωr |i × ~zr |i ) = ~ r |i ∗ (~zr |i × ~xr |i )
ω
~yr |i ∗ (~
ωr |i × ~zr |i ) = ~ r |i ∗ (~zr |i × ~yr |i )
ω
With
~ r |i ∗ (~yr |i × ~xr |i )
ω = −ω
~ r |i ∗ ~zr |i
~ r |i ∗ (~zr |i × ~xr |i )
ω = ~ r |i ∗ ~yr |i

~ r |i ∗ (~zr |i × ~yr |i )
ω = −ω
~ r |i ∗ ~xr |i
and because the entries of S are mirrored (with changing sign) along its zero
line:
 
0 −ω~ r |i ∗ ~zr |i + ω
~ r |i ∗ ~yr |i
S =  +ω ~ r |i ∗ ~zr |i 0 −ω~ r |i ∗ ~xr |i 
−ω ~ r |i ∗ ~yr |i + ω
~ r |i ∗ ~xr |i 0
 
~ r |i ∗ ~xr |i
ω
=  ω ~ r |i ∗ ~yr |i  ×
~ r |i ∗ ~zr |i
ω
= ~ r |r ×
ω
~ r |r .
That prooves that ~s = ω 

d
So the result for RT · dt m(t)
~ |i is:
d d d
RT · m(t)
~ |i = ~ r |r × ~n(t) |r +
ω ~n(t) |r + RT · m ~ 0 (t) |i
dt dt dt
d d
We can now express our law as a function of ~n(t) |r , n(t) |r , dt
dt ~ ~ 0 (t) |i
m and
~ r |r :
ω

f (~ ~
α(t), β(t)) = g(~γ (t),~(t)) (1)

6
with
α
~ (t)= ~n(t) |r + m~ 0 (t) |r (2)
~ ~
~γ (t) = k(t) |r + j0 (t) |r (3)
~ d d
β(t) = S · ~n(t) |r + ~n(t) |r + RT · m ~ 0 (t) |i (4)
dt dt
d d
~(t) = S · ~k(t) |r + ~k(t) |r + RT · ~j0 (t) |i (5)
dt dt
Whereas originally it was
d d
f (m(t)
~ |i ,
m(t)
~ |i ) = g(~j(t) |i , ~j(t) |i ) (6)
dt dt
There are two cases to which this result applies:
Case 1 (coordinate vectors):
If ~n(t) and m(t)
~ are intended to be vectors pointing to the same point
P (namely coordinate vectors) in the law, then the orientation of vector
~n(t) |r varies with the shift of origin m
~ 0 (t) |i . We want to express our law
in coordinates of a moving frame. We have
m(t)
~ |i = R · ~n(t) |r + m
~ 0 (t) |i ~j(t) |i = R · ~k(t) |r + ~j0 (t) |i (7)

Equations (1) - (6) apply.


Case 2 (vectors immune to shifting):
If the law relates ~n(t) and m(t)
~ as vectors which are not spacebound, then
they are one and the same thing. The shift m ~ 0 (t) |i has to be equal to
zero. Equation (7) becomes:
m(t)
~ |i = R · ~n(t) |r ~j(t) |i = R · ~k(t) |r (8)
= ~n(t) |i = ~k(t) |i
Equations (1) - (6) change a bit:
~
f (ζ(t), ~η (t)) = ~
g(θ(t), ~
ϑ(t)) (9)
with
~
ζ(t) = ~n(t) |r (10)
~
θ(t) = ~k(t) |r (11)
d
~η (t) = S · ~n(t) |r + ~n(t) |r (12)
dt
~ d
ϑ(t) = S · ~k(t) |r + ~k(t) |r (13)
dt
Whereas originally it was
d d
f (m(t)
~ |i , m(t)
~ |i ) = g(~j(t) |i , ~j(t) |i ) (14)
dt dt

Вам также может понравиться